2011
DOI: 10.4038/sjae.v4i0.3485
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Intra-household Allocation of Food: A Case Study of the Urban Poor in Kandy

Abstract: Malnutrition among children and women continues to be one of the major problems in Sri Lanka despite the food and nutritional intervention programs implemented since independence. The objectives of this study were to find out whether there is calorie malnutrition among the urban poor in Kandy and to find out the determinants of the intra-household allocation of calories. Calorie adequacy ratios of fathers, mothers and children were compared to find out whether there is calorie malnutrition among family members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Sampled nuclear families with both parents alive, non-working women (for high caste) and working women (for Scheduled Tribe). t -testAvailability of food (lean vs peak season)Cereal intake – Recommended cereal intakes for a balanced diet Harriss-White [27]1991Longitudinal 4x 1 day 24h176 HHSix villages in central and southern India.Men and women (age not specified) t -test• Season• Region• Land holding vs landlessRI = Relative calorie intakes (Individual intakes / Adult male intakes)Nepal ( n  = 1) Gittelsohn [9]1991Cross-sectional 1x 1 day 24h & observation115 HHSix villages in Western hills. Men and women aged 18-24, 25-49, and ≥50CorrelationFood serving habits, including serving order, asking for food, having second helpings, substituting foods, and channelling foods.FQS = Food quantity score (individual consumption as a proportion of total household consumption / Individual body weight as a proportion of total household body weight)Pakistan ( n  = 1) Government of Pakistan [38]1979Cross-sectional1x 24h975 HHMale head of household, plus woman of childbearing age (preferably pregnant or lactating) and all children aged under 3 years.Linear regression (coefficients not reported)• Education• Region• Household size• IncomeIndividual intake / Household intake (calories, protein, iron and vitamin A)Sri Lanka ( n  = 1) Rathnayake and Weerahewa [30]2002Cross-sectional1x 24h60 HHHouseholds from lower income group in urban Kandy.Fathers and mothers (age not specified)Linear regression coefficient and t -test• Mother’s income• Mother’s education• Ethnicity• Family sizeRCA = Relative calorie allocation (calorie intake as a proportion of recommended allowance / Household intake as a proportion of household allowance) WFR Weighed food records, 24h 24-hour dietary recall, HH Households …”
Section: Resultsmentioning
confidence: 99%
“…Sampled nuclear families with both parents alive, non-working women (for high caste) and working women (for Scheduled Tribe). t -testAvailability of food (lean vs peak season)Cereal intake – Recommended cereal intakes for a balanced diet Harriss-White [27]1991Longitudinal 4x 1 day 24h176 HHSix villages in central and southern India.Men and women (age not specified) t -test• Season• Region• Land holding vs landlessRI = Relative calorie intakes (Individual intakes / Adult male intakes)Nepal ( n  = 1) Gittelsohn [9]1991Cross-sectional 1x 1 day 24h & observation115 HHSix villages in Western hills. Men and women aged 18-24, 25-49, and ≥50CorrelationFood serving habits, including serving order, asking for food, having second helpings, substituting foods, and channelling foods.FQS = Food quantity score (individual consumption as a proportion of total household consumption / Individual body weight as a proportion of total household body weight)Pakistan ( n  = 1) Government of Pakistan [38]1979Cross-sectional1x 24h975 HHMale head of household, plus woman of childbearing age (preferably pregnant or lactating) and all children aged under 3 years.Linear regression (coefficients not reported)• Education• Region• Household size• IncomeIndividual intake / Household intake (calories, protein, iron and vitamin A)Sri Lanka ( n  = 1) Rathnayake and Weerahewa [30]2002Cross-sectional1x 24h60 HHHouseholds from lower income group in urban Kandy.Fathers and mothers (age not specified)Linear regression coefficient and t -test• Mother’s income• Mother’s education• Ethnicity• Family sizeRCA = Relative calorie allocation (calorie intake as a proportion of recommended allowance / Household intake as a proportion of household allowance) WFR Weighed food records, 24h 24-hour dietary recall, HH Households …”
Section: Resultsmentioning
confidence: 99%
“…Also, studies suggested that a proper nutrition knowledge impact on good nutrition status [38]. Insufficient nutrition-related knowledge of women is an underlying cause for the high prevalence of undernutrition and micronutrient deficiencies [39][40][41], as women's nutritional knowledge affects attitudes and eating behaviour [14]. One of the studies suggested that women's inadequate nutrition knowledge and their food intake did not meet all the nutritional requirements of pregnancy [42].…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings, it was important to notice that even though mother's income affected household calorie adequacy ratio in both urban and rural sectors, the direction of the impact was different; mothers' income had a positive effect on calorie adequacy ratio in rural sector while it was negative in urban sector. The result for the urban sector is similar to the findings of study done by themselves previously (Rathnayake and Weerahewa 2002). Further the study found that mother's education affects positively to the calorie adequacy in urban sector, while father's education affects negatively.…”
Section: Determinants Of Food Security: Urban Rural Differencessupporting
confidence: 89%